A persistent Kuroshio in the glacial East China Sea and implications for coral paleobiogeography - Vogt-Vincent, N; Mitarai, S (Wiley, 2020)
The Kuroshio Current is a major hydrographical feature of the modern East China Sea, but it has been suggested that its flow was diverted to the east of the Ryukyu Arc at the Last Glacial Maximum. Shoaling of the Yonaguni Depression has also been proposed as a cause of Kuroshio Current diversion which, while unlikely to have been significant at the Last Glacial Maximum, may have been an important consideration further back in time. Using an ensemble of high‐resolution ocean simulations with climatic boundary conditions emulating those of the Last Glacial Maximum, we present the first regional state estimates of the glacial East China Sea which are both physically consistent and compatible with sea surface temperature proxy compilations. We find that while the Kuroshio Current transport in the East China Sea is slightly reduced at the Last Glacial Maximum, its path is relatively unchanged, with limited sensitivity to glacioeustatic sea level change, glacial‐interglacial changes in climate, and tectonic shoaling of the Yonaguni Depression. Simulations with the best model‐proxy agreement predict only limited contraction of the reef front at the Last Glacial Maximum, and strong surface currents associated with the glacial Kuroshio may have maintained or even improved long‐distance coral larval dispersal along the Ryukyu Arc, suggesting that conditions may have enabled coral reefs in this region to remain widespread throughout the last glacial. Further field studies investigating whether this is genuinely the case will provide insights into how the coral reef front responds to long‐term environmental change.